The dimensionality of the hare psychopathy checklist-revised, revisited: Its purported multidimensionality might well be artifactual. (1st February 2019) - Maraun, Michael D.; Metta, Alessandro; Hart, Stephen D.; Fraser-Maraun, Jason; Heene, Moritz
Abstract: Investigation into the structure of Hare's Psychopathy Checklist-Revised (PCL-R) has consistently shown it to be multidimensional. The implications of multidimensionality for the scale are nontrivial. In the first place, because the construct of psychopathy has traditionally been considered to be dimensional and unitary, results seeming to show that the PCL-R is multidimensional could be taken as calling into question the construct validity of the scale as a measure of psychopathy. In the second, unidimensionality is the sole psychometric justification for employing a composite of test items to scale individuals. Herein, we argue that the purported multidimensionality might, in actuality, be an artifact of the grounding of dimensionality assessment on species of dimensionality- those specific to principal component and linear factor analysis- which are incongruous with the scale. A reconsideration of the scale's theoretical structure singles out the unidimensional monotone latent variable (UMLV) brand of unidimensionality as the one appropriate to the role of grounding dimensionality assessments of the PCL-R. Empirical support for this position is provided by a small-scale dimensionality analysis informed by the UMLV sense of unidimensionality.